Strengthening women's capacity through ecoprint batik making training in realizing the sustainable development goals - Septi Wulandari; Hanuun Salsabila; Vania Diva Damainingrum (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Ecoprint making is one of the opportunities that can be done by the community, especially women, particularly in this digital era to increase income. The training on ecoprint-making in Mojorejo Village targets women from various professions, including housewives, sewing groups, PKK mothers, and others. This is one of the leading work programs chosen by the community service team. The community service team chose this work program with the aim of empowering women through training and mentoring programs for making ecoprint batik. Additionally, the ecoprint-making training tends to be more straightforward and easier to follow. This work program is a leading program due to its simple method, easy-to-find materials, and ability to produce high-value products. We carry out this training in stages, incorporating lecture methods, question and answer sessions, practical exercises, and modules. This training activity resulted in the creation of ecoprint products made directly by participants, such as tote bags, cloth, and headscarves. This activity results in the cessation of the Standard Operating Procedure for running the Ecoprint program under the village's auspices.